MANAJEMEN RETRIBUSI ANGKUTAN UMUM PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KOTA PALU - Mohammad, Irma (Katalogis, 2016)
This research aims at identifying and analyzing the management of public transport retribution. This research uses descriptive qualitative, Terry’s measurements (2008; 40) consist of planning, organizing, actuating and controlling. Based on data collection, it was concluded that the implementation of the planning function in the context of preparing the work program of the retribution amount targets of public transport, has not been implemented based on a feasibility study by identifying, presenting alternative options, and then setting it up. In a sense, targeting public transport retribution revenues has not applied planning functions conceptually yet. Implementation of the organizing functions or organizing people involved in the activity of the targets achievement of public transport retribution has been conducted well but it has not been able to integrate the duties and functions of field workers with proper remuneration. Implementation of actuating function by the leader is merely directed at achieving the target of public transport retribution, and it is not focused on how to move staff or officer by fulfilling the needs adequately. Implementation of the supervision function has not been conducted effectively because it tends to be done indirectly in the form of oral and written reports. While direct supervision is being left entirely to the coordinator of field supervisors who are vulnerable to abuse the authority. Based on these descriptions, it indicates that the implementation of functions of management in the management of public transport retribution is not maximal yet, and it is causing the retribution targeted annually is not achieved.